LINC00673 rs11655237 C>T Polymorphism Impacts Hepatoblastoma Susceptibility in Chinese Children - Yang, Tianyou; Li, Jiahao; Wen, Yang; Tan, Tianbao; Yang, Jiliang; Pan, Jing; Hu, Chao; Yao, Yuxiao; Zhang, Jiao; Xin, Yijuan; Li, Suhong; Xia, Huimin; et al. (Frontiers in Genetics, 2019)
Background: Hepatoblastoma (HB) is the most common hepatic malignancy in children, accounting for approximately 80% of all childhood liver tumors. Previous genome-wide association studies (GWASs) have found that the LINC00673 rs11655237 C>T polymorphism is associated with the risk of several different adult cancers. However, the association between this polymorphism and HB susceptibility remains unclear. Methods: We analyzed the association between the LINC00673 rs11655237 C>T polymorphism and HB susceptibility in a hospital-based study of Chinese children. We enrolled 213 HB patients and 958 healthy controls with genotypes determined by TaqMan, and the strength of the association of interest was determined by calculating odds ratios (ORs) and 95% confidence intervals (CIs). Findings: We found a significant association between the LINC00673 rs11655237 C>T polymorphism and HB risk (CT/TT compared with CC: adjusted OR=1·40, 95% CI=1·04–1·88, p=0·029). Furthermore, stratified analysis indicated that rs11655237 T allele carriers in the following subgroups were more likely to develop HB: children older than 17 months, males, and those with tumors of clinical stages III + IV. Interpretation: In conclusion, we confirmed that the LINC00673 rs11655237 C>T polymorphism may be associated with HB susceptibility. Prospective studies with larger sample sizes and patients of different ethnicities are needed to validate our findings.